“Protección del desarrollo de productos elaborados en la carrera de agroindustria a través del secreto industrial de un caramelo (toffe) elaborado con la adición de lactosuero, y manjar elaborado a base de leche y suero lácteo”. - Tipan Chuquitarco, Blanca Graciela (2024)
The Technical University of Cotopaxi, throughout the Faculty of Agricultural Sciences and Natural Resources, always committed to research and improvement of technical processes for the creation of new products, allows this work to be carried out, the objective of which is to protect through industrial secrecy the products made with the addition of whey: toffee caramel and delicacy produced from milk. To carry out the legalization of intellectual property, the required information was obtained from flow charts, process methodology and formulations of products prepared in research work from previous cycles. Counseling was attained from a lawyer specialized in knowledge of intellectual property procedures, who carried out the necessary legal process for this work’s suitable registration. The process that was carried out for legitimation was the protocolization and notarization of the two recipes in the Third Notary of Latacunga canton. Then, a request was written to SENADI (National Intellectual Rights Service), who were responsible for registering the industrial secret. All this led to obtain and hold the intellectual property rights of the toffee candy and the delicacy on behalf of Technical University of Cotopaxi. Thus, preventing other people from having easy access to the industrial secret and from being able to make replicas of the recipes without having authorization or having made any agreement with the institution. Finally, the result of the integrative project managed to obtain the safety of the industrial procedure of the product recipes and was delivered for safekeeping to the Technical University of Cotopaxi.